(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
This essay examines the relationship between the history of trauma narratives and the development of media representations. Starting in the late 19th century, modernist cultures were increasingly forced to represent and reflect upon the traumatic experience of destruction and war. In this process of reflection, the ‘invisibility’ or unrepresentability of traumatic incidents became a recurring theme. Taking up W.J.T. Mitchell’s suggestion that all media are “mixed media,” I argue that the technological, semiotic, and narrative hybridity of mixed media has a special relationship to this theme. More specifically, I want to show that the explicit or overt presentation of mixed media has historically been invoked as a trope of reflexivity and a way of expressing the difficulties of representing traumatic experience. I will begin my investigation with literary and visual examples from American modernism and conclude with more recent instances of mixed media hybrids combining analogue and digital media.